Has Political Decentralisation Brought Progressive Institutional Changes to Indonesia?* - Mokoginta, Ivantia (P2E-LIPI, 2013)
Political decentralisation in Indonesia has not necessarily brought progressive institutional changes leading to a more democratic society at the local level. When social capital is embedded in the ceremonially warranted patterns of behaviour, that is, patrimonial behaviour, the increase in social capital is restricted to the business-bureaucrat-politico networks – the local political oligarchies. As a result, the increase in social capital at the local level is likely to be wasted by rent collecting. This is the reason progressive institutional changes remain far from complete, at least in the medium term. This paper also shows what could be done and what has been accomplished to push forward progressive institutional changes